Gender Differences in the Effects of Behavioral Problems on School Outcomes - Jannie H. G. Kristoffersen; Nina Smith (Institute for the Study of Labor (IZA), 2013)
Behavioral problems are important determinants of school outcomes and later success in the labor market. We analyze whether behavioral problems affect girls and boys differently with respect to school outcomes. The study is based on teacher and parent evaluations of the Strength and Difficulties Questionnaire (SDQ) of about 6,000 children born in 1990-92 in a large region in Denmark. The sample is merged with register information on parents and students observed until the age of 19. We find significant and large negative coefficients of the externalizing behavioral indicators. The effects tend to be larger when based on parents' SDQ scores compared to teachers' SDQ scores. According to our estimations, the school outcomes for girls with abnormal externalizing behavior are not significantly different from those of boys with the same behavioral problems. A decomposition of the estimates indicates that most of the gender differences in Reading and Math cannot be related to gender differences in behavioral problems. The large overall gender gap in Reading seems mainly to be the result of gender differences between children without behavioral problems living in 'normal families', i.e. families which are not categorized as low-resource families.
Keywords: J16; I29; I19; 330; gender differences; education; behavior